An efficient and cost-effective method for directed mutagenesis at multiple dispersed sites—a case study with Omicron Spike DNA. Issue 1 (22nd December 2022) - Rani, Rita; Parsa, Kishore V L; Chatti, Kiranam; Sevilimedu, Aarti
Abstract: Site-directed mutagenesis is an invaluable technique that enables the elucidation of the contribution of specific residues to protein structure and function. The simultaneous introduction of mutations at a large number of sites (>10), singly and in multiple combinations, is often necessary to fully understand the functional contributions. We report a simple, efficient, time and cost-effective method to achieve this using commonly available molecular biology reagents and protocols, as an alternative to gene synthesis. We demonstrate this method using the Omicron Spike DNA construct as an example, and create a construct bearing 37 mutations (as compared to wild-type Spike DNA), as well as 4 other constructs bearing subsets of the full spectrum of mutations. We believe that this method can be an excellent alternative to gene synthesis, especially when three or more variants are required. Graphical Abstract: